Measurement of food reinforcement in preschool children: Associations with food intake, BMI, and reward sensitivity - Rollins, Brandi Y. (Appetite, 2013)
Progressive ratio (PR) schedules of reinforcement have been used to measure the relative reinforcing value (RRV) of food in humans as young as 8 years old; however, developmentally appropriate measures are needed to measure RRV of food earlier in life. Study objectives were to demonstrate the validity of the RRV of food task adapted for use among for preschool children (3 to 5y), and examine individual differences in performance. Thirty-three children completed the RRV of food task in which they worked to access graham crackers. They also completed a snack task where they had free access these foods, liking and hunger assessments, and their heights and weights were measured. Parents reported on their child’s reward sensitivity. Overall, children were willing work for palatable snack foods. Boys and older children made more responses in the task, while children with higher BMI z-scores and reward sensitivity responded at a faster rate. Children who worked harder in terms of total responses and response rates consumed more calories in the snack session. This study demonstrates that with slight modifications, the RRV of food task is a valid and developmentally appropriate measure for assessing individual differences in food reinforcement among very young children.